2020
DOI: 10.47153/jbmr14.442020
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Islamic Bank's Performance Using CAMELS And RGEC Method Based On Indonesian Financial Services Authority Circular

Abstract: This paper aims to determine the differences bank performance of Muamalat BankBank Sinarmas Bank, and BPRS Bhakti Sumekar measured by CAMELS (Capital, Asset, Management, Earning, Liquidity, Sensitivity to Market Risk) method and the RGEC (Risk profile, Good governance, Earning, Capital) method in 2018. The authors used quantitative methods with a descriptive approach. The sample taken in this study is a representation of Islamic commercial banks (Bank Muamalat), Islamic business unit banks (Bank Sinarmas Syari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The RGEC approach, which is based on the Financial Services Authority Regulation Number 8/POJK.03/2014, serves as a template for evaluating the soundness level of Islamic commercial banks and their business units. Banks must undertake a standalone or consolidated assessment of their soundness level using the RGEC method (Abdullah, 2020). The bank soundness level assessment process involves scrutinizing various factors, including the Risk Profile, Good Corporate Governance, Earnings, and Capital of the bank.…”
Section: Rgec Methods (Risk Profile Good Corporate Governance Earning...mentioning
confidence: 99%
“…The RGEC approach, which is based on the Financial Services Authority Regulation Number 8/POJK.03/2014, serves as a template for evaluating the soundness level of Islamic commercial banks and their business units. Banks must undertake a standalone or consolidated assessment of their soundness level using the RGEC method (Abdullah, 2020). The bank soundness level assessment process involves scrutinizing various factors, including the Risk Profile, Good Corporate Governance, Earnings, and Capital of the bank.…”
Section: Rgec Methods (Risk Profile Good Corporate Governance Earning...mentioning
confidence: 99%
“…If the NPF value is low, it means that the financing problems faced by the bank are also low, but if the value is high, the bank is experiencing high financing problems. So it can be concluded that the higher the NPF value, the greater the losses experienced, therefore bank profits will also decrease, and vice versa, the lower the NPF value, the higher the profits (Abdullah, 2020). Research conducted by (Irwin Muslimin et al, 2023) shows that NPF has a significant negative impact on ROA.…”
Section: Non Performing Finance (Npf)mentioning
confidence: 99%
“…13/24/DPNP dated October 25, 2011 (Bank Indonesia, 2011), which demands banks, including Islamic, to assess their soundness level based on risk using the RGEC (Sari & Lestari, 2022). The RGEC framework includes Risk Profile, Good Corporate Governance, Earnings, and Capital Adequacy, which assesses a bank's vulnerability to risk, managerial quality, profit generation, and capacity to withstand losses (Abdullah, 2020).…”
Section: Introductionmentioning
confidence: 99%